Use of Information and Communication Technologies as a Tool by Elementary School Teachers of Social Studies - Chaves Choza, Johana (2023)
One of the main characteristics of the Digital Era is the inclusion of Information and Communication Technologies (ICT) in the different facets of daily life, particularly in education and its incorporation in classroom dynamics. Based on this, a proposal of educational strategies is presented through the use of technological tools for approaching the subject of Social Studies in the fourth year of primary school, for which the quantitative approach was used to diagnose the level of knowledge about ICT as a tool in the educational process by the teaching staff of the fourth year of primary school in the subject of Social Studies during the first semester of 2019 and the perception of the fourth year students on the use of technological tools in the classroom. It was possible to detect gaps in knowledge about ICT, frequency of use, methodology employed, strategies used, types of tools, roles and teaching approaches. At the same time, aspects such as the sporadic use of technological tools stand out, of which the television under a behaviorist model and the low knowledge of ICT by the teaching staff are noticeable. The results obtained were used as the basis for the design of the proposal.